Análise geoestatística do “vira-cabeça” na cultura do tomateiro - Quartezani, Waylson Zancanella; Hell, Leonardo Raasch; Cunha Junior, Jadier de Oliveira; Moraes, Willian Bucker; Belan, Leônidas Leoni; Moraes, Simone de Paiva Caetano Bucker; De Jesus Junior, Waldir Cintra; Furtado, Edson Luiz [UNESP] (FapUNIFESP (SciELO), 2018)
Considering the various diseases that reduce tomato crop production, the virosis known as “vira-cabeça” is highlighted. Epidemics of this disease are frequent, showing high progress rates and expressive damage. In this case, studies about the space-time variability can help propose management strategies. Therefore, the aim this study was to map the spatial distribution of tospovirus incidence over time in a tomato crop in order to understand the dispersal mechanisms of this pathogen and the disease progress. Thus, the presence or the absence of symptoms of this disease was monitored over time in 120 georeferenced plants, arranged in a regular mesh and distributed in a spacing of 1.0 x 0.5 m. The disease incidence data were subjected to the geostatistical analysis. After the adjustment of semivariograms, interpolation of data was performed by means of kriging. There was epidemic of the disease in tomato crop, and the progress rate (Dy/Dt) varied from 4.7 to 6 diseased plants/day, while 100% plants exhibited symptoms at 20 days after the first detection of the disease on the crop. There was strong spatial dependence of the distribution of tomato plants with symptoms of “vira-cabeça” in all assessments, and the reach value varied from 4.3 to 1.69 m. Over time, secondary foci of the disease emerged, as well as lateral expansion and coalescence of the latter, characterizing dispersion due to the action of the vector agent associated with initial inoculum sources, internal and external to the tomato crop. The random pattern of the disease distribution progressed to aggregated and subsequently regular.
Geostatistical analysis of tospovirus in tomato crop
Keywords: Kriging; Solanum lycopersicum; Space-time; TSWV